2019
DOI: 10.1038/s41598-019-49867-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeted multiplex proteomics for molecular prescreening and biomarker discovery in metastatic colorectal cancer

Abstract: Protein biomarkers are widely used in cancer diagnosis, prognosis, and prediction of treatment response. Here we introduce the use of targeted multiplex proteomics (TMP) as a tool to simultaneously measure a panel of 54 proteins involved in oncogenic, tumour suppression, drug metabolism and resistance, in patients with metastatic colorectal cancer (mCRC). TMP provided valuable diagnostic information by unmasking an occult neuroendocrine differentiation and identifying a misclassified case based on abnormal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…We found that expression of EGFR and its dimerization partners is common in KRAS G12C CRC and NSCLC clinical samples. Basal EGFR expression, as measured by immunohistochemistry or mass spectrometry (28,29), has not been associated with EGFR inhibitor sensitivity in CRC, and indeed we find no clear difference between receptor expression levels by lineage or in the subset of CRC and NSCLC patients treated with AMG510. In cell line models, however, we are able to assess activated RTK levels and we find that the degree of this dependency on RTK signaling across KRAS G12C mutant tumors can be very different.…”
Section: Discussionmentioning
confidence: 57%
“…We found that expression of EGFR and its dimerization partners is common in KRAS G12C CRC and NSCLC clinical samples. Basal EGFR expression, as measured by immunohistochemistry or mass spectrometry (28,29), has not been associated with EGFR inhibitor sensitivity in CRC, and indeed we find no clear difference between receptor expression levels by lineage or in the subset of CRC and NSCLC patients treated with AMG510. In cell line models, however, we are able to assess activated RTK levels and we find that the degree of this dependency on RTK signaling across KRAS G12C mutant tumors can be very different.…”
Section: Discussionmentioning
confidence: 57%
“…Proteomics, as a valuable tool to unravel the biochemical changes, is rapidly developed and become a useful laboratory tool to improve cancer management from early detection to the exploitation of therapeutic strategies (Serna et al, 2019). iTRAQ (isobaric tags for relative and absolute quantitation) by a multiplexed set of reagents for quantitative protein analysis that place isobaric mass labels at the N termini and lysine side chains of peptides in a digest mixture, is an emerging quantitative proteomic method with great speed and accuracy (Guo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such developments will facilitate research by providing detailed functional information, like for example the activity of specific pathways (65,67). On the other hand, less complex but more robust targeted acquisition approaches will likely become more relevant in clinical settings and could complement antibody-based detection for diagnosis and stratification (88)(89)(90). Biochimica Et Biophysica Acta Bba -Proteins Proteom 1844, 917-926 33.…”
Section: Discussionmentioning
confidence: 99%